Diversos patogenos fungicos - Schwartz, Howard F. (International Center for Tropical Agriculture, 1980)
Bean plants are exposed to many fungal diseases; among these are: Alternaria and Ascochyta leaf and pod spots, ashy stem blight (Macrophomina phaseoli), Cercospora leaf spot, Chaetoseptoria leaf spot, Diaporthe pod blight, downy mildew (Phytophthora parasitica), Entyloma leaf smut, floury leaf spot (Ramularia phaseoli), gray mold (Botrytis cinerea) gray leaf spot (Cercospora vandersysti), Phyllosticta leaf spot, white leaf spot (Pseudocercosporella albida), powdery mildew (Erysiphe polygons) and the yeast spot (Nematospora coryll). Infection may occur on seedlings or adult plants during the growing season or after harvesting. Some affect production sightly; but as cultural practices are modified, it may severely limit production in the future. The symptoms and damage caused by the diseases are illustrated in color. (CIAT)